Renewable energy in Antarctica - Photovoltaic for Neumayer Station III - Franziska Bockelmann; Ann-Kathrin Dreier; Joris Zimmermann; Markus Peter (Solar Energy Advances, 2022)
A feasibility study on the topic of expanding renewable energies in Antarctica at Neumayer Station III (NM3) has been conducted. Today, the station is mainly operated with polar diesel in combination with combined heat and power plants, resulting in high CO2 emissions (714 t/a). By mapping the station in the simulation program TRNSYS, different expansion scenarios of the core components combined heat and power plants, wind turbines, photovoltaic systems, battery storage and thermal storage were considered. To investigate station operation and the interactions between the individual components, their number and dimensions were varied within a feasible range in a separate parameter study for each component. Criteria for the design of the components were, in addition to redundancy and security of supply, maximization of the share of renewable energy, reduction of CO2 emissions and economic efficiency. The concept with the economic and ecological aims to achieve for AWI includes a PV system with 44 kWp and a thermal storage system of 10 m³ in addition to five new CHP units, five wind turbines and a battery storage system with 300 kWh. With this variant, up to 65 % coverage by renewable energies and a reduction in CO2 emissions of 43 % can be achieved in the 10 % expansion scenario (increase in energy demand at the power plant). To increase the share of renewables, the new concept must follow the power-to-heat approach, which in turn increases the electricity demand. Wind turbines make the largest contribution to increasing the share of renewables. Another focus was placed on the role of the PV system in the overall concept. Due to the limited space available at the station, the PV system has only a small impact of 3 to 7 percentage points on increasing the share of renewable energy. Despite the small impact, the use of a PV system has only advantages, as it improves the concept both ecologically and economically and contributes to a diversification of energy sources.